PEDAGOGICAL POSSIBILITIES OF DEVELOPING TECHNOLOGICAL SKILLS BASED ON ROBOTICS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the theoretical and practical aspects of using robotics elements in developing children's technological thinking in preschool educational organizations. The importance of innovative approaches in the modern education system is analyzed, particularly their role in forming logical thinking, creativity, and problem-solving skills in young children.